Dietrich Bonhoeffer and the ethical self Christology, ethics, and formation - Elliston, Clark J. (Minneapolis Fortress Press, 2016)
This volume argues that Bonhoeffer's early work, particularly his Christocentric anthropology, grounds his later expressed commitments to responsibility and faithfulness in a ""world come of age."" Ellison suggests, in fact, that a concern for otherness permeates all of Bonhoeffer's work: a Christian self-defined by its orientation towards otherness
Includes bibliographical references (pages 205-211) and indexes
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Bonhoeffer, Dietrich -- 1906-1945; Christian Ethics